MerTK inhibition decreases immune suppressive glioblastoma-associated macrophages and neoangiogenesis in glioblastoma microenvironment. Issue 1 (3rd June 2020) - Su, Yu-Ting; Butler, Madison; Zhang, Meili; Zhang, Wei; Song, Hua; Hwang, Lee; Tran, Andy D; Bash, Ryan E; Schorzman, Allison N; Pang, Ying; Yu, Guangyang; Zamboni, William C; et al.
Abstract: Background: Glioblastoma-associated macrophages and microglia (GAMs) are the predominant immune cells in the tumor microenvironment. Activation of MerTK, a receptor tyrosine kinase, polarizes GAMs to an immunosuppressive phenotype, promoting tumor growth. Here, the role of MerTK inhibition in the glioblastoma microenvironment is investigated in vitro and in vivo. Methods: Effects of MRX-2843 in glioblastoma microenvironment regulation were determined in vitro by cell viability, cytokine array, in vitro tube formation, Western blotting, and wound healing assays. A syngeneic GL261 orthotopic glioblastoma mouse model was used to evaluate the survival benefit of MRX-2843 treatment. Multiplex fluorescent immunohistochemistry was used to evaluate the expression of CD206, an anti-inflammatory marker on GAMs, and angiogenesis in murine brain tumor tissues. Results: MRX-2843 inhibited cell growth and induced apoptosis in human glioblastoma cells and decreased protein expression of phosphorylated MerTK, AKT, and ERK, which are essential for cell survival signaling. Interleukin-8 and C-C motif chemokine ligand 2, the pro-glioma and pro-angiogenic cytokines, were decreased by MRX-2843. Decreased vascular formation and numbers of immunosuppressive (CD206+) GAMs were observed following MRX-2843 treatment in vivo, suggesting that in addition to alleviating immunosuppression, MRX-2843 also inhibits neoangiogenesis in the glioma microenvironment. These results were supported by a prolonged survival in the syngeneic mouse orthotopic GL261 glioblastoma model following MRX-2843 treatment. Conclusion: Our findings suggest that MRX-2843 has a therapeutic benefit via promoting GAM polarization away from immunosuppressive condition, inhibiting neoangiogenesis in the glioblastoma microenvironment and inducing tumor cell death.